ICT investment and GDP growth: Causality analysis for the case of Korea. (August 2021) - Sawng, Yeong-wha; Kim, Pang-ryong; Park, JiYoung
Abstract: This study investigated how investment in the industry of Information, Communication and Technology (ICT) has been interlocked with the GDP growth of South Korea. Based on seasonally-adjusted quarterly time-series data for the period between 1999 and 2016 available from the Korea Statistical Information Service, a Vector Error Correction model was applied for the analysis. The results revealed that ICT investment and GDP growth affected bi-directionally except for the short-run case in which only ICT investment affected GDP growth. The results explain that ICT investment plays an important role in the economic growth of South Korea in the long term; at the same time, investment size in the ICT industry increases as the economy grows. Without controlling any other factors, we found GDP increases by 0.4% when ICT investment increases by 1%. However, in the short term, only ICT leads to GDP growth. Therefore, the recent stagnation in ICT investment experienced in South Korea could negatively affect the economic growth of Korea in the short run, and hence, in the long-run, if it should become prolonged. The ICT investment strategy revealed from this study is especially useful to policy-makers who plan the economic growth in South Korea and other ICT-advanced countries because promoting ICT utilization across all sectors requires putting legal and policy mechanisms in place. Highlights: Using VECM, this study could examine ICT investment in Korea has been interlocked with the GDP growth of South Korea. ICT investment and GDP growth affected bi-directionally in the long-run. In the short-run, ICT investment has led the Korean GDP growth. An ICT investment strategy can gear the economic growth in South Korea and other ICT-advanced countries.